“Técnicas de intervención psicopedagógicas, en el desarrollo de la lectoescritura de los niños del segundo año de educación general básica de la escuela “Presidente Jaime Roldós”, del cantón laTtroncal, provincia del Cañar durante el período académico, enero - septiembre 2015” - Urquizo Orozco, Danny Rolando (2017)
The professional work of psychopedagogy is developed in the school educational context establishing theoretical, ideological positions, ethical conceptions of subjects such as psychology, pedagogy and social work, among others, which are focused on processes related to the way they learn. For these reasons, this thesis theme is presented as follows: "Techniques of Psychopedagogic Intervention in the Development on “President Jaime Roídos” School second graders’ Literacy, located at La Troncal city, province of Cafiar during the academic period, January-September 2015."Its main purpose is to demonstrate how the psychopedagogical intervention techniques through motivational exercises, visual discrimination exercises and palmo-digital exercises develop literacy in second graders. The theoretical framework contains the scientific and essential definitions of the scientific contents of the two variables; psychopedagogical techniques and literacy in the development of the work. All the topics were used to establish the indicators of the observation instrument. The technique used was the observation with the application of a tab as an instrument. It was applied to the 38 children considered as the universe of the investigation. It was carried out in two moments; before and after the application of the Psychopedagogical Intervention Guide. These techniques, and instrument allowed the researcher to collect the data to be tabulated and graphically represented, analyzed and interpreted. The research design was non-experimental, explanatory and descriptive. The type of research was laboratory, correlational and transversal, the methods used were scientific, hypothetical deductive, analytical and synthetic. In order to compare the results before and after the application of the Psychopedagogical Techniques Guide and to probe the hypotheses, both general and specific, the Z statistic of proportions method was used. The final chapter describes the conclusions and recommendations that yielded the results of research.